A Combination of Robotic Approach and ERAS Pathway Optimizes Outcomes and Cost for Pancreatoduodenectomy. Issue 6 (June 2019) - Kowalsky, Stacy J.; Zenati, Mazen S.; Steve, Jennifer; Esper, Stephen A.; Lee, Kenneth K.; Hogg, Melissa E.; Zeh, Herbert J.; Zureikat, Amer H.
Abstract : Objective: To determine the impact of enhanced recovery after surgery (ERAS) pathway implementation on outcomes, and cost of robotic and open pancreatoduodenectomy. Background: ERAS pathways have shown benefit in open pancreatoduodenectomy (OPD). The impact of ERAS on robotic pancreatoduodenectomy (RPD) is unknown. Methods: Retrospective review of consecutive RPD and OPDs in the pre-ERAS (July, 2014–July, 2015) and ERAS (July, 2015–July, 2016) period. Univariate and multivariate logistic regression was used to determine impact of ERAS and operative approach alone, or in combination (pre-ERAS + OPD, pre-ERAS + RPD, ERAS + OPD, ERAS + RPD) on length of hospital stay (LOS) and overall cost. Results: In all, 254 consecutive pancreatoduodenectomies (RPD 62%, OPD 38%) were analyzed (median age 67, 47% female). ERAS patients had shorter LOS (6 vs 8 days; P = 0.004) and decreased overall cost (USD 20, 362 vs 24, 277; P = 0.001) compared with non-ERAS patients, whereas RPD was associated with decreased LOS (7 vs 8 days; P = 0.0001) and similar cost compared with OPD. On multivariable analysis (MVA), RPD was predictive of shorter LOS [odds ratio (OR) 0.33, confidence interval (CI) 0.16–0.67, P = 0.002), whereas ERAS was protective against high cost (OR 0.57, CI 0.33–0.97, P = 0.037). On MVA, when combining operative approach with ERAS pathway use, a combined ERAS + RPD approach was associated with reduced LOS and optimal cost compared with other combinations (pre-ERAS + OPD, pre-ERAS + RPD, ERAS + OPD). Conclusion: ERAS implementation is independently associated with cost savings for pancreatoduodenectomy. A combination of ERAS and robotic approach synergistically decreases hospital stay and overall cost compared with other strategies. Abstract : Supplemental Digital Content is available in the text